(untitled) (Journal of Research Updates in Polymer Science, 2013)
The report has a double character: it deals with the synthesis and preparation of a series of polymers based on bisphenol-A (BPA) monomer; a series of physical and thermomechanical properties are examined for one type (diglycidyl ether of BPA, DGEBA with nanosilica) of the prepared materials. The reactions involved in diepoxy curing with a diamine, functional group modelling for cross-linked polymers, formation of a polymer DGEBA, BPA polyaddition to DGEBA forming a polyether, DGEBA curing with Jeffamine and cross-linking to form a resin are analyzed. Nanocomposites of silica, coated with cross-linked epoxy–amine, are synthesized and examined by 29Si-magic-angle-spinning nuclear magnetic resonance and Fourier-transform infrared spectroscopies, thermogravimetric and dynamic mechanical analyses, differential scanning calorimetry and scanning electron microscopy. Epoxy matrix is filled with nanosilica to design materials with defined properties. A low weight percentage of filler results in matrix improvement.